The dubious disciples: doubt and disbelief in the post-resurrection scenes of the four gospels - Woodington, J. David (Zeitschrift für die neutestamentliche Wissenschaft und die Kunde der älteren Kirche, 2020)
Frontmatter -- Contents -- Acknowledgments -- 1 Introduction -- 2 The Gospel Of Mark -- 3 The Gospel Of Matthew -- 4 The Gospel Of Luke -- 5 The Gospel Of John -- Conclusion -- Appendix: The Disciples In Ancient Christianity -- Bibliography -- Index